Mejoramiento de la calidad higiénico sanitaria de la leche de los sistemas bovinos del cantón el Carmen - Buste Sabando, María Guadalupe (2019)
The present investigation had the purpose of obtaining a diagnosis of the sanitary hygienic conditions of the farmers´ milk of El Carmen canton. For this purpose, a survey was applied as a notified tool to a sample of farmers of a finite population of the canton in the subsequent study, an observation sheet containing a checklist to verify the information obtained at the beginning of the research process, the next step will be to sample the milk for both physicochemical analyzes (pH, acidity , density, alcohol test, total solids, ashes, fat, protein) as microbiological (E. coli, reductase and mesophilic aerobes) where these results were evaluated and considering the shortcomings that must be corrected, competition was provided to ASOGAN partners with the objective of which they can improve the good practices of milking and manipulations of the milk, to continue the monitoring and evaluation of the results before and after the binary logistic transmission was carried out, obtained through binary logistic regression determined that there was no significant statistical difference for the physicochemical and microbiological variables of the milk in the sampled farms, evidencing that when applying the Good Milking Practices the quality of the milk is improved in comparison with the unsampled farms.